HUMAN RIGHTS AND REGIONAL COOPERATION IN AFRICA: SADC AND THE CRISIS IN ZIMBABWE (The Strategic Review for Southern Africa, 2020)
Since the early 1990s African regional and continental organisations have been playing an active role in maintaining military security and promoting democracy, good governance and respect for human rights in Africa. However, their efforts have often proved ineffective. This article contributes to the analysis of the causes of the difficulties African multilateral organisations have been facing in promoting democracy and human rights on the continent through a case-study of SADC's policy towards the crisis in Zimbabwe. The article shows that SADC efforts aimed at restoring democracy and putting an end to human rights abuses in Zimbabwe were critically hampered by the history of political antagonism among the Southern African governments, and by SADC's inability to draw a clear distinction between respect for human rights and the promotion of a neoliberal strategy of regional development. In the end, SADC diplomatic efforts were caught between the demagogic rhetoric of the ZANU-PF regime as represented by President Mugabe, and the international consensus on development. SADC ultimately proved unable to both help redress the deep economic and social inequalities in Zimbabwe and uphold human rights in the country
Keywords: Zimbabwe; African regional and continental organisations; military security; multilateral organisations; democracy; human rights; Southern African governments; SADC; ZANU-PF; neoliberal strategy